Mechanical, microstructural, and thermal characterization insights of pyrolyzed carbon black from waste tires reinforced epoxy nanocomposites for coating application - Verma, Akarsh; Baurai, Kriti; Sanjay, M. R.; Siengchin, Suchart (Polymer composites, 2020)
Pyrolysis is a viable technique to convert waste tires into recyclable products, as the dumping of these scrap tires pose a serious environmental threat. In the present investigation, a detail methodology to fabricate and characterize the carbonaceous filler (in the form of nanocarbon black obtained from pyrolysis of waste tires) modified epoxy resin composites has been retrieved. The composites with varying carbon filler content (0, 5, 10, and 15 wt%) were fabricated using the manual hand lay‐up and compression molding techniques. The morphological analysis (field‐emission scanning electron microscopy test) revealed that the synthesized pyrolytic carbon black was in nanoscale and uniformly dispersed in the epoxy matrix. Various physical (density and water absorption), mechanical (tensile, compression, flexural, hardness, and impact), electrical and thermal (differential thermal analysis and thermogravimetric analysis) tests were done to completely examine the nanocomposite developed. We found that the 5 wt% of carbon black in epoxy resin exhibited the best mechanical properties and was complemented by the microstructural (scanning electron microscopy and X‐ray diffraction) tests analysis. High tensile strength and hardness than neat epoxy resin makes this composite a potential candidate for polymer coatings in automotive industries.